Effects of Sepak Takraw based on Neo-Humanist Approach with Inside-Foot Touch Skills - Chumkhotr, Komkrissada; Tingsabhat, Suthana (An Online Journal of Education, 2021)
The purpose of this research was to study the effects of Sepak Takraw based on Neo-Humanist approach on inside foot touch skills, between the experimental group which received inside foot touch skill with Neo-Humanist approach and the control group which received inside foot touch skill with conventional approach. The participants of the study were 60 lower secondary school students in both genders. The students were purposively selected and equally divided into the experimental group and the control group. Researchers developed eight learning activity plans and the data were collected by using the inside foot touch skills test. The item of objective congruent (IOC) of the learning activity plans and the inside foot touch skills test were 0.85 and 0.83 respectively. The experimental group was trained inside foot touch skill with Neo-Humanist approach for 8 weeks, once a week for 50 minutes. The obtained data were statistically analyzed to compare t-test score of the inside foot touch skill test and knock board test between experimental group and control group before and after the implementation by using statistically significant differences at .05 level. The results of the research were as follows: 1) The Sepak Takraw learning management based on Neo-Humanist approach was able to develop inside foot touch skills of the students. 2) The mean scores of the inside foot touch skill test of both experimental group and control group after implementation were significantly higher than the scores before implementation at 0.5 level. 3) The mean scores of the inside foot touch skill test of the experimental group students after implementation were significantly higher than the scores of the control group at 0.5 level